Experimental and numerical analysis on rectangular concrete-filled steel tubular columns with T-shaped stiffeners. (January 2022) - Chen, Shaozhen; Liu, Yuan; Luo, Jinhui; Gao, Shuyu
Abstract: Rectangular concrete-filled steel tubular (RCFST) columns are widely used in mega frame-core tube-outrigger truss super high-rise buildings, yet the local buckling of the steel tube may cause a large amount of waste on the steel material. In order to resolve this problem, this paper investigates the axial compression behavior of giant RCFST columns with T-shaped stiffeners by means of experimental and numerical analysis. Firstly, axial compression tests on 12 RCFST columns are conducted. The experimental results indicate that T-shaped stiffeners can improve the ultimate bearing capacity of RCFST columns, and the effect is more significant with the increase of the width-to-thickness ratio of the steel tube. However, T-shaped stiffeners have little effect on improving the ductility of axial compression members. Secondly, finite element (FE) models are established using ABAQUS and are verified against the experimental results. Subsequently, detailed parametric analysis and theoretical derivation are conducted based on the validated FE models. The results reveal the variation law of critical buckling stress and failure mode with respect to stiffness ratio. Finally, the design equations and procedures of T-shaped stiffeners in RCFST columns are obtained, by which the cross-section size of T-shaped stiffeners can be optimized, leading to a more economical design. Highlights: Axial compression tests on 12 RCFST columns are conducted. Finite element models are established using ABAQUS and are verified against the experimental results. Detailed parametric analysis and theoretical derivation are conducted. The variation law of critical buckling stress and failure mode with respect to stiffness ratio is obtained. The design equations and procedures of T-shaped stiffeners in CFST columns are obtained.